Intracerebral Hemorrhage in the Oldest Old: A Population-Based Study (Vantaa 85+) - Tanskanen, Maarit; Mäkelä, Mira; Myllykangas, Liisa; Rastas, Sari; Sulkava, Raimo; Paetau, Anders (Frontiers in Neurology, 2012)
Aims: Very elderly subjects represent the fastest growing population in the world. Most of the recent studies on intracerebral hemorrhage (ICH) have been carried out on younger patients and/or preferably using novel radiological techniques. We investigated the prevalence, risk factors, and histopathological characteristics of the ICH in the oldest old. Materials and methods: The brains of 300 autopsied individuals (248 females, 52 males, mean age at death 92.4 ± 3.7 years) were investigated as part of the prospective population-based Vantaa 85+ study. After macroscopic investigation, the presence and extent of microscopic brain hemorrhages (MH) were analyzed by counting the number of iron containing macrophages (siderophages) by Prussian blue staining. Deposits with >5 siderophages were defined as MH+, forming a subgroup of MH. Genotyping of apolipoprotein E (APOE) and the analysis of microscopic (MI) or larger infarctions and cerebral amyloid angiopathy (CAA) were performed using standardized methods. Regression analysis was used to predict the presence of ICH, with and without co-localized CAA, and was adjusted for age at death and gender. Results: The prevalence of macroscopic ICH was 2.3% in total; consisting of 1% large lobar hemorrhage (LH), 1% deep hemorrhage (DH), and 0.3% of subarachnoid hemorrhage (SAH). 62% had MH and 15.3% MH+. All MH+ lesions were found to be >2 mm wide. 55.9% of subjects with MH and 81.2% of those with MH+ showed MH/MH+ and CAA in the same brain region (MHCAA and MH+CAA, respectively). MH was associated with none of the neuropathological or clinical conditions, nor with the APOE carrier status. The subjects with MH+, MHCAA or MH+CAA carried the APOE ε4 allele more frequently than controls (OR 3.681, 3.291, 7.522, respectively). Siderophages in MH+CAA co-localized with CAA and with two-thirds of the MI in the tissue sections. Conclusion: Macroscopic ICH was rare in the very elderly. MH was frequent and clinically insignificant. MH+ was rare but closely related with the APOE ε4 genotype and the presence of severe CAA and infarction.